Audit and accounting guide : depository and lending institutions : banks and savings institutions, credit unions, finance companies, and mortgage companies. (American Institute of Certified Public Accountants, Inc., 2017)
The 2017 edition of this industry standard resource offers clear and practical guidance of audit and accounting issues such as transfers and servicing, troubled debt restructurings, financing receivables and the allowance for loan losses, and fair value accounting. It also provides direction for institutions assessing their operations and internal controls for regulatory considerations as well as discussions on existing regulatory reporting matters. Updates include: SAS No. 132, The Auditor's Consideration of an Entity's Ability to Continue as a Going Concern SSAE No. 18, Attestation Standards: Clarification and Recodification Note: FASB ASU No. 2016-13 will have a significant impact on the guide; however, incorporation of guidance will not occur until the 2018 or 2019 edition of the guide.